Suicidal ideation, suicide attempts and sexual harassment among transgender people in Puducherry, South India: a cross sectional analytical study - Selvaraj, Manimozhi; Sarkar, Sonali; Rajkumar, Ravi Philip (International Journal Of Community Medicine And Public Health, 2023)
Background: Transgender people are stigmatized, victimized and often driven towards attempting suicide due to institutionalized discrimination. We aimed, to determine the proportion and factors associated with suicidal ideation in last one year and suicide attempts in their lifetime and the proportion of transgender people who have faced sexual harassment in Puducherry. Methods: It was a cross sectional analytical study. All consenting adult transgender residing in Puducherry and registered with SCOHD (NGO) were included in the study. Pre-tested semi structured questionnaire was used as study tools (C-SSRS and TGISS). Suicidal ideation, suicide attempts and sexual harassment were expressed in proportion and multivariate analysis was done to find the independent association of variables with the outcomes using adjusted prevalence ratios. Results: Of the 119 transgender people who participated in this study, 50% were unemployed and 28.6% were involved in sex work. Overall prevalence of suicidal ideation, suicide attempts and sexual harassment was found to be 31.1% (95%CI 23.3%-39.8%), 46.2% (95%CI 37.4%-55.2%) and 84.87% (95%CI 77.5%-90.4%) respectively. In multivariate analyses, suicidal ideation was significantly associated with higher income; suicide attempts were associated with being employed. Conclusions: Lack of support from the family and friends and the stigmatizing behaviour of the society were the causes of their fear of living in the society. Extreme forms of stigma ultimately leads to their suicidal behaviour.